How (not) to interpret a non-causal association in sports injury science - Hjerrild, M.; Videbaek, S.; Theisen, D.; Malisoux, L.; Nielsen, R. O. (Physical Therapy in Sport, 2018)
Objective: To discuss the interpretability of non-causal associations to sports injury development exemplified via the relationship between navicular drop (ND) and running-related injury (RRI) in novice runners using neutral shoes. Design: 1-year prospective cohort study. Setting: Denmark. Participants: 926 novice runners, representing 1852 feet, were included. Main outcome measure: The outcome was "a musculoskeletal complaint of the lower extremity or back caused by running, which restricted the amount of running for at least a week". Results: Fewer feet with small ND than those feet with a reference ND sustained injuries at 50 (risk difference (RD)?=?-4.1% [95%CI=-7.9%;-0.4%]) and 100km (RD=-5.3% [95%CI=-9.9%;-0.7%]). Similarly, fewer feet with a large ND sustained injuries than the feet with a reference drop at 250 (RD=-7.6% [95%CI=-14.9%;-0.3%]) and 500km (RD=-9.8% [95%CI=-19.1%;-0.4%]). Conclusion: Non-causal associations can help to identify sub-groups of athletes at an increased or decreased risk of sports injury. Based on the current results, those with a small or large navicular drop sustain fewer injuries than those with a reference drop. Importantly, navicular drop does not cause RRIs, but influences the relationship between training load and RRI. This illustrates that non-causal associations are unsuitable to respond to the question: Why do sports injury develop?